„On the other side of the border”. The media in strengthening an international dialogue (the Czech-German Journalism Award) - Olechowska, Paulina (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2018)
The purpose of this article is to describe the role and significance of the Czech-German Journalism Award in creating a dialogue between journalist circles in both countries (the Czech Republic and the Federal Republic of Germany). Their competition is a tool for developing strategic external communication between the two nations, the aim of which is to strengthen mutual understanding. A structural and qualitative analysis of text was used as the research method, while the mission was to describe the kinds of publishers/broadcasters awarded and characterize the problems discussed in the award-winning works of the two editions of the Award held to date.

Celem artykułu jest próba określenia roli i znaczenia Czesko-Niemieckiej Nagrody Dziennikarskiej w tworzeniu dialogu pomiędzy środowiskami dziennikarskimi obu krajów (Republika Czeska i Republika Federalna Niemiec). Mający bilateralny charakter konkurs jest narzędziem strategicznej komunikacji zewnętrznej dwóch krajów, którego celem jest umacnianie porozumienia pomiędzy narodami. Jako metodę badawczą zastosowano strukturalną i jakościową analizę treści, zadanie polegało na: wskazaniu rodzajów nagrodzonych wydawców/nadawców oraz określeniu poruszanej tematyki w zwycięskich pracach konkursowych dotychczasowych dwóch edycji Cz-NNDz.
„Po drugiej stronie granicy”. Media w umacnianiu międzynarodowego dialogu na przykładzie Czesko-Niemieckiej Nagrody Dziennikarskiej
Keywords: Czech-German Journalism Award; strategic external communication (media relations); cross-border journalism; Czesko-Niemiecka Nagroda Dziennikarska; strategiczna komunikacja zewnętrzna (media relations); dziennikarstwo transgraniczne